Społeczne uwarunkowania sprawności procesu zmian - Pluta, Anna (Social conditions of the change process efficiency, 2006)
The article presents that success of contemporary enterprises depends not only on the dynamics of implementing changes but also on the creativity of individuals within them. The creativity of management staff influence an originality of implemented changes and the employees' acceptance of the change process. The author implies that management staff with creative characteristics create culture that favorites changes, especially through their ability to diagnose possibilities and limitations, building an atmosphere of confidence and open communication within company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 383-389